PROCEDURAL ASPECTS OF EU STATE AID LAW - Pošćić, Ana (EU and comparative law issues and challenges series (ECLIC), 2018)
The article will discuss the main features of different procedural rules on EU State Aid law. The monitoring system of state aid control is based on ex ante verification pursuant to Article 108(3) TFEU. Since the European Commission has a central role, special emphasis will be on four different types of procedures: the procedure regarding notified aid, the procedure regarding unlawful aid, the misused aid procedure and the existing aid procedure.